Influencing gender-inclusive climate change policies in Latin America - Gumucio, Tatiana; Tafur Rueda, Mariana (Africa Centre for Gender, Social Research and Impact Assessment, 2015)
This paper provides an overview of the state of gender inclusion in national policies related to climate change in seven target countries of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in Latin America. A rubric for evaluating policies’ levels of gender integration was developed based on guidelines and methods for gender inclusion. Preliminary findings suggest that gender-sensitive consultation processes and increased efforts at cross-sectoral coordination can lead to successful gender integration in climate change planning.